种瓣结鱼湖泊网箱生态养殖方法 (2017)
本发明公开了种瓣结鱼湖泊网箱生态养殖方法，包括如下步骤：选择区域和网箱：选择在湖泊中开阔、向阳的水域进行网箱养殖，水质清新且无污染；网箱双层，网箱中设有饲料台；在鱼种入箱前1周，将网箱放置在普通塘口中；苗种投放：每个网箱放养800尾体长为3-3.5cm的瓣结鱼种，每个网箱还搭配有50尾30-35g/尾的花白鲢鱼种；饲料投喂：5月时日投喂饲料量占体重的1.5-2％，6-9月时日投喂饲料量占体重的3-5％，10月时日投喂饲料量占体重的1-1.5％，11月时停止投喂饲料；每日将饲料投放于饲料台上，每天上午8点时投喂日投喂饲料量的35-45％，下午5点时投喂日投喂饲料量的55-65％；日常管理。 The invention discloses a tor-brevifilis lake net cage ecological aquaculture method. The tor-brevifilis lake net cage ecological aquaculture method includes the following steps: selecting an area and net cages, wherein the wide and apricus water area in a lake is selected for net cage aquaculture, water is fresh and free of pollution, the net cages are of double-layer structures, feed tables are arranged in the net cages, and the net cages are placed in common pond openings at the time one week before fries are placed into the net cages; breeding the fries, wherein the 800 young tor-brevifilises with the body lengths ranging from 3 cm to 3.5 cm are bred in each net cage, and the 50 chub fries with the sizes ranging